The runaway bunny. - Brown, Margaret Wise, 1910-1952.; Hurd, Clement, 1908-1988 (New York, Harper & Row, 1972)
A little rabbit who wants to run away tells his mother how he will escape, but she is always right behind him.
Keywords: Rabbits -- Fiction; Mother and child -- Fiction